Legal Implications of Law No. 1/1974 and the Compilation of Islamic Law on The Validity of Adult Marriage in Indonesia (A Comparative Analysis of Positive Law, Islamic Law, and Customary Law in Determining the Legality of a Marriage) - Yazidi, Nur Syifa; Silva, Sonia Dhea; Al Amruzi, M Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This article highlights the legal impact of Law No. 1 of 1974 and the Compilation of Islamic Law (KHI) on the recognition of customary marriage in Indonesia, by examining the comparison between national law, Islamic law, and customary law in determining the validity of a marriage. Indonesia as a country rich in culture has a variety of customary marriage practices, which often conflict with state and religious laws, especially regarding the obligation to register marriages. Law No. 1 of 1974 states that a marriage is valid if it is carried out according to each religion and is officially registered, while the KHI also emphasizes the importance of registration for the order of Muslim administration. However, some indigenous people consider customary rituals to be sufficient to validate a marriage without the need for state registration, thus raising legal issues related to the status of their spouses and children, especially in terms of identity and inheritance rights. This study uses a normative legal method with a statutory and comparative approach, comparing the three legal systems and examining the applicable regulations. The results of the study indicate the potential for conflict and legal uncertainty due to differences in the criteria for the validity of marriage between state law, Islamic law, and customary law. Therefore, harmonization efforts are needed to create legal certainty while still respecting the cultural diversity of Indonesian society.